Demoralised but not depraved: Why societal lack of norms disheartens people but does not necessarily make them commit moral transgressions - Maksymenko, O. (Социология: теория, методы, маркетинг, 2019)
Since the early days of sociology, the anomie phenomenon has interested many social scientists. A number of theories have been developed, a host of empirical studies (including cross-national) have been performed since Emile Durk heim described this phenomenon and introduced the anomie term. Still, there is no general consensus among scholars on what anomie is and what it is not. A hard-and-fast definition of anomie has not yet been given, and what is more, researchers look at this phenomenon from at least two different perspectives: individual and institutional, explaining it as a state of mind or a state of society respectively. In terms of society, anomie has mostly been associated with malfunctioning social institutions and breakdown of moral standards, as is evidenced by high crime rates and public justification of unethical behaviour. On the other hand, living even in a "totally anomic" society and experiencing a whole range of anomie-driven emotions and reactions does not necessarily mean acting immorally. To what extent is the thesis about a link between anomie and moral decline of society applicable at individual level? The author seeks to answer this question.